IMPROVEMENT OF TEACHER’S COMPETENCE AT EARLY CHILDHOOD CURRICULUM BY EDUCATING IN KKG JENDRAL SOEDRIMAN I, EAST PURWOKERTO - Widiasari, Yuki; Hapsari, Melati Ismi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
2013’s curriculum was used in many level of education, one of them is preschool. Based of the rule is PP No. 32 Tahun 2013. The problem at KKG Gugus Jendral Soedirman I is how to used this curriculum on activities at preschool. Focused of this movement is saintific learning and authentic assessment. So, we have two programmes for solve the problem; (1) Learning Saintific’s Education. Educating start with find saintific concept and then save it to our mind. After each of teacher understanding this object, we are following with applicating saintific learning in six aspects growing dan development. Cognitive, physic, linguistic, social emotional, religi, and art, (1) Authentic Assessment’s Education. This action start with explaining deepth information about authentic assessment. Then, the teacher have time to assesst used anechdot and daily note. Both of them used to arrange daily assessment. There are two outcome’s of this project, 1) lesson planning and 2) assessment rubric